New Contribution to the Diversity of the Anaerobic Genus Metopus (Ciliophora, Armophorea), With Descriptions of Three New Marine Species - Zhuang, Wenbao; Li, Ran; Feng, Xiaochen; Al-Farraj, Saleh A.; Hu, Xiaozhong (Frontiers in Marine Science, 2022)
Armophorean ciliates constitute an important component of microeukaryotic community in anaerobic or hypoxic environments. Yet, their diversity remains poorly known due to under-sampling or the scarcity of knowledge. In this study, three metopid ciliates, i.e., Metopus paraes sp. n., Metopus spiculatus sp. n., and Metopus parapellitus sp. n., collected from coastal sediments in Qingdao and Rizhao, China, were investigated using live observation, protargol staining, and molecular phylogenetic methods. M. paraes sp. n. can be distinguished by its long caudal cilia. M. spiculatus sp. n. resembles M. vestitus in many ways, but differs mainly in having a beak-like preoral dome end and a conspicuous tail. The most remarkable features of M. parapellitus sp. n. include an ovate body shape, caudal cilia located at the rear end and right posterior body, and an adoral zone that never extends onto the dorsal surface. Sequence divergences supported the species identification of these three species. Phylogenetic analyses confirmed that the Metopus is not monophyletic, and first revealed that all marine species of Metopus form a well-supported clade. The clustering of these marine forms with M. es (type species) is not rejected by the AU test, which infers that the marine clade represents the genus Metopus together with M. es.